OCEANIC LITHOSPHERE 1. The Origin and Evolution of Oceanic Lithosphere: Introduction - Malpas, John; Robinson, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary During the past 25 years much has been learned about the structure and composition of oceanic lithosphère through bathymétrie surveying, seismic experiments, and scientific drilling. Our understanding of the processes by which oceanic lithosphère is generated is still limited, however, by our inability to sample directly the lower crust and upper mantle.This is due to the limitations of available drilling platforms, the technological challenges of drilling on bare rock close to mid-ocean ridges, and the inordinate expense of drilling deep holes through the ocean crust. Exposed ophiolites offer a valuable alternative source of information on oceanic lithosphère but their interpretation is hampered by uncertain provenance, tectonic dismemberment, and overprinting of original features during emplacement. Using data from studies of in situ oceanic lithosphère and ophiolites, numerous models have been developed for the genesis of oceanic crust and upper mantle which involve the interaction of a variety of magmatic, tectonic and hydrothermal processes. These models can only be tested thoroughly by deeper ocean drilling.